A List of Damselflies (Zygoptera: Odonata) Recorded from Azad Jammu and Kashmir, Pakistan (Biological Sciences - PJSIR, 2008)
. In the intensive survey of the valley of Kashmir for updating the record of damselflies inhabiting the region, a total of 15 genera and 31 species of damselflies were collected during the summer season of three consecutive years (2005-2007) which are reported.